Enhancing Resource Use Efficiency (RUE) in Indoor Vertical Farming Systems (PACER) - MUHAMMAD FAUZAN; PROF. MADYA Dr. AKMAL NIZAM BIN MOHAMMED; Mohd Faizal Mohideen Batcha; Sulastri Sabudin (Research Progress in Mechanical and Manufacturing Engineering, 2026)
Indoor vertical farming systems offer high productivity but require efficient management of resources. The effect of inefficient management of resources will lead to increase in operational cost and reduce sustainability. This study aim to evaluate and enhance Resource Use Efficiency (RUE) in indoor farming system operated at PACER UTHM. The methodology involved conducting water, energy, nutrient and Carbon Dioxide audits. Performance are analyzed relative to crop yield, the indicator involved are Water Use Efficiency (WUE), Energy Use Efficiency (EUE), Nutrient Use Efficiency (NUE) and Carbon Dioxide Use Efficiency (CUE). The finding shows that WUE is 1.3052, while EUE is 0.1717. NUE obtained are 11.1935 and CUE are 45.8351. The outcomes provides insight into sustainable indoor farming practices and support the development of more efficient resource controlled environment.